2021
DOI: 10.1111/1440-1630.12718
|View full text |Cite
|
Sign up to set email alerts
|

Using the Work Behaviour Inventory and Work Environment Impact Scale to measure employment sustainability for people with severe mental illness in a vocational rehabilitation program

Abstract: People with severe mental illness often have difficulty sustaining employment. Work Behaviour Inventory and Work Environment Impact Scale are vocational assessments used by occupational therapists to evaluate the facilitators and barriers of work performance and work environment respectively. These factors may have an impact on job tenure and can inform occupational therapy practice. Methods: This study analysed retrospective data of 85 clients who attended a 3-month Employment Internship Program from August 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Previous studies [ 33 ] have also indicated that high attendance at training is a factor influencing the employment of people with mental disabilities using employment training facilities. These studies also indicated that good work habits impact finding [ 34 ], returning [ 35 ], and continuing to work [ 36 ]. These findings suggest that support for increasing habituation to continue working is important for the ability to work.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [ 33 ] have also indicated that high attendance at training is a factor influencing the employment of people with mental disabilities using employment training facilities. These studies also indicated that good work habits impact finding [ 34 ], returning [ 35 ], and continuing to work [ 36 ]. These findings suggest that support for increasing habituation to continue working is important for the ability to work.…”
Section: Discussionmentioning
confidence: 99%
“…Workplace characteristics may have an impact on employment retention and require further study. Evidence can be found, for example, on the importance of workplace social networks [ 69 ], job matching [ 70 ], job satisfaction [ 71 ], time demands [ 72 , 73 ] and supervisor interaction [ 74 ]. These factors were not taken into account in this study, which reduces the strength of the results.…”
Section: Discussionmentioning
confidence: 99%